Pemberdayaan Kelompok Petani Garam Kristal Geomembran Gampong Neuheun Melalui Branding Kemasan dan Diversifikasi Produk Sabun Cuci Tangan Berbasis Garam - Prajaputra, Vicky; Gusti Vonna, Adinda; Isnaini, Nadia; Waliul Perdana, Adli; Amri MC, Ulil; Meutia Panggabean, Dara; Annura Rezkina, Cutwan; Auriza Putri, Rizka; Musfira, Rifqi; Nurzima; Arifqi, Muhammad; Azizah, Nurfiah; Jannah, Raudhatul; Dibya Shahieza, Najmi; Nabil Firzatullah, Muhammad (Universitas Mataram, 2025)
This community service program focuses on the empowerment of the geomembrane crystal salt farmers group in Gampong Neuheun, Aceh Besar Regency, through product innovation based on salt derivatives and the strengthening of branding strategies. The program aims to enhance the farmers’ capacity, skills, and economic welfare by increasing the added value of their salt products. The activities were conducted at the Training Center of Syiah Kuala University for the socialization and training sessions, and at the farmers’ production site for hands-on practice. The implementation adopted a participatory training approach, consisting of program socialization, salt-based hand wash production, salt refining and packaging practice, and evaluation through pre-test and post-test assessments. The evaluation results showed a significant improvement in participants’ competencies. A total of 62.29% of participants demonstrated an excellent understanding of the hand wash production process, 78.57% mastered the use of tools and materials, and 85.71% showed good comprehension of branding and marketing strategies. All participants (100%) expressed high enthusiasm and willingness to participate in future training. The resulting hand wash product exhibited soft foam, a fresh aroma from patchouli oil, and effective cleansing properties, while raw salt was successfully processed into 250 g refined packaged salt under the brand “Merak Bintang Global”, increasing its market value by approximately 40% compared to bulk salt. Overall, the program effectively enhanced the participants’ technical and entrepreneurial skills while strengthening the competitiveness of local salt products through innovation, branding, and product diversification based on coastal potential.